Modern folk works about the Muscovites: between folklore and post-folklore consciousness (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2025)
The article examines the problems of determining the formal and semantic indicators of modern folklore and its connections with the modern social reality of the Ukrainians. Nowadays the trend in folklore is the study of folklore phenomena according to the new socio-political and cultural conditions of cooperation between the personality and the team; problems of determining the phenomena of folklorism, folklorization and non-folklore thinking. This article emphasis on understanding folklore as a process of adaptation, transformation and reproduction of folklore in everyday life, culture and art with an emphasis on its social and artistic reasons, which determine the entry of a genetically literary work within the “artistic canon” of folk art. It is pointed out active modern folklorization processes in the Ukrainian cultural space. Folklorization is interpreted as the introduction of a folk work into oral circulation from printed sources, from the stage or from the media. It is also noted that, along with traditional folklore, which continues to function actively, the cultural life of society includes postfolklore, which is interpreted in the article as a qualitatively new cultural product related to digital consciousness (cyber-folklore, newslore, Internet folklore) and diagnosed state of development of modern social values and cultural codes. Special attention is focused on the active existence of folk works about the Muscovites in the conditions of Russian aggression, in which the lexical unit “moscal” acquires new connotations. The researched works are conceived as samples that are on the border of folklore and post-folklore consciousness. Today folklore innovations, which appear on the basis of traditional social and moral and ethical stereotypes, accumulation of folklore experience, through the prism of which the reality is understood, often having an oral type of existence, may contain audiovisual component, intertextual component and spread rapidly in modern cultural space and illustrate modern understanding of reality.
Keywords: folklore; postfolklore; tradition; folklorization